Long-Term Enrichment of Stress-Tolerant Cellulolytic Soil Populations following Timber Harvesting Evidenced by Multi-Omic Stable Isotope Probing - Wilhelm, Roland C.; Cardenas, Erick; Leung, Hilary; Szeitz, András; Jensen, Lionel D.; Mohn, William W. (Frontiers in Microbiology, 2017)
Soil management is vital for maintaining the productivity of commercial forests, yet the long-term impact of timber harvesting on soil microbial communities remains largely a matter of conjecture. Decomposition of plant biomass, comprised mainly of lignocellulose, has a broad impact on nutrient cycling, microbial activity and physicochemical characteristics of soil. At ‘Long-term Soil Productivity Study’ sites in California dominated by Ponderosa pine, we tested whether clear-cut timber harvesting, accompanied by varying degrees of organic matter (OM) removal, affected the activity and structure of the cellulose-degrading microbial populations sixteen years after harvesting. Using a variety of experimental approaches, including stable isotope probing with 13C-labelled cellulose in soil microcosms, we demonstrated that harvesting led to a decrease in net respiration and cellulolytic activity. The decrease in cellulolytic activity was associated with an increased relative abundance of thermophilic, cellulolytic fungi (Chaetomiaceae), coupled with a decreased relative abundance of cellulolytic bacteria, particularly members of Opitutaceae, Caulobacter and Streptomycetaceae. In general, harvesting led to an increase in stress-tolerant taxa (i.e. also non-cellulolytic taxa), though our results indicated that OM retention mitigated population shifts via buffering against abiotic changes. Stable-isotope probing improved shotgun metagenome assembly by 20-fold and enabled the recovery of ten metagenome-assembled genomes of cellulolytic bacteria and fungi. Our study demonstrates the putative cellulolytic activity of a number of uncultured taxa and highlights the mineral soil layer as a reservoir of uncharacterized diversity of cellulose-degraders. It also and contributes to a growing body of research showing persistent changes in microbial community structure in the decades following forest harvesting.